The relationship between iron deficiency anemia with restless leg syndrome and sleep quality in workers working in a textile factory in Iran: a cross-sectional study - Farahnaz Ghahremanfard; Maryam Rezaei Semnani; Majid Mirmohammadkhani; Kamyar Mansori; Daryoush Pahlevan (Middle East Current Psychiatry, 2023)
Abstract Background The aim of this study is to investigate the relationship between iron deficiency anemia with restless leg syndrome (RLS) and sleep quality in workers working in a textile factory in Iran. This cross-sectional study was conducted on 216 workers working in a textile factory in Iran. In addition to demographic and occupational variables, Pittsburgh Sleep Quality Index (PSQI) and RLS questionnaires were used for the data collection. To investigate iron deficiency anemia, 2 CC of blood was taken from the brachial artery with the help of a 10-CC syringe with a blue or pink tip. Then, relevant data were entered into SPSS26 and analyzed. Results The mean (S. D.) age of the workers was 32.23 (6.14) and 60.6% of them were women. The prevalence of iron deficiency anemia was 21.2 and 69.5% in men and women, respectively. Most of the workers were in moderate condition in terms of RLS severity, and 78.2% had sleep disorders. There was an inverse and significant correlation between age (β= −0.200), work experience (β= −0.160), hemoglobin (β= −0.149), and ferritin (β= −0.186) with global PSQI score (P value<0.05). Also, an inverse and significant correlation was observed between age (β= −0.164), hemoglobin (β= −0.548), and ferritin (β= −0.410) with RLS score (P value<0.05). However, there was a direct and significant correlation between TIBC level and RLS score (β= 0.227) and global PSQI score (β= 0.395) (P value<0.05). Conclusions Intervention programs to reduce iron deficiency anemia and periodic screening programs to identify sleep disorders and RLS in textile factory workers seem necessary.